The Effect of Date Consumption on Increasing Hemoglobin Levels in Female Teenagers at State Senior High School 2 Rambah Hilir - Masdi Janiarli; Eka Yuli Handayani; Rahmi Fitria; Rasmi (CV. AFDIFAL MAJU BERKAH, 2025)
Adolescents are young people aged 10-19 years who are susceptible to anemia. Anemia is one of the problems that still occurs in the world today. The World Health Organization (WHO) noted that more than 30% of the world's population suffers from anemia, with a prevalence of around 40-88% in developing countries, including Indonesia. Anemia can be treated non-pharmacologically by giving dates. Dates are fruits that provide many benefits for the body, one of which is to increase hemoglobin levels and treat anemia because dates are rich in calcium and iron. This study was conducted at SMA Negeri 2 Rambah Hilir. The purpose of the study was to determine the effect of giving dates on increasing hemoglobin levels in female adolescents at SMA Negeri 2 Rambah Hilir. This type of research is quantitative research with a Pre-Experimental Research Design with a Group Pretest-Posttest design. The sample in the study was 25 people. Sampling used the Purposive Sampling technique. Data analysis used the Dependent T test. The average result of the respondents' hemoglobin levels before and after giving dates was -2.79 with a standard deviation of 2.02 and a standard error of 4.53. The dependent T test obtained a P value = 0.000 < 0.05, which means that the p value <0.05. So it can be concluded that there is an effect of giving dates on increasing hemoglobin levels in female adolescents at SMA Negeri 2 Rambah Hilir. It is expected that after the study, respondents can consume dates to increase hemoglobin levels and avoid the use of pharmacological drugs